The association of megalin and cubilin genetic variants with serum levels of 25-hydroxvitamin D and the incidence of acute coronary syndrome in Egyptians: A case control study - Raghda A. Elsabbagh; Mohamed F. Abdel Rahman; Sally I. Hassanein; Rasha S. Hanafi; Reem A. Assal; Gamal M. Shaban; Mohamed Z. Gad (Journal of Advanced Research, 2020)
Megalin and cubilin are two receptors that mediate endocytosis of 25-hydroxyvitamin D (25(OH)D) for its final activation by hydroxylation. The aim of the present study was to evaluate the association of polymorphisms in megalin (rs2075252 and rs4668123) and cubilin (rs1801222 and rs12766939) with the circulating serum levels of 25(OH)D and with the early incidence of acute coronary syndrome (ACS) in Egyptians. The study included 328 subjects; 185 ACS patients aged between 27 and 60 years, and 143 healthy age-matched controls. Genotyping of cubilin rs12766939 Single Nucleotide Polymorphism (SNP) was performed using Real-Time Polymerase Chain Reaction (qPCR) and for megalin rs4668123 and rs2075252 and cubilin rs1801222 by Polymerase Chain Reaction- Restriction Fragment Length Polymorphism (PCR-RFLP). 25(OH)D levels were measured by Ultra Performance Liquid Chromatography- Tandem Mass Spectroscopy (UPLC-MS/MS). Results showed that vitamin D deficiency was highly linked to ACS incidence (P < 0.0001). The megalin rs4668123 CC, cubilin rs1801222 GG and cubilin rs12766939 GG + GA genotypes are associated with a higher ACS incidence and can be considered risk factors, according to Chi-squared test (P = 0.0003, 0.0442, 0.013 respectively). Conversely, the megalin rs2075252 SNP was not associated with increased ACS incidence. However, after performing multiple logistic regression analysis, only the megalin rs4668123 SNP was considered an independent ACS risk factor. Furthermore, the megalin rs4668123 CC genotype was associated with lower 25(OH)D levels (P = 0.0018). In conclusion, megalin rs4668123 (CC) was linked to lower 25(OH)D levels and can be considered an independent risk factor for incidence of ACS. Keywords: Acute coronary syndrome, Cubilin, Egyptians, Megalin, Polymorphisms, Vitamin D receptor